Manufacturing of ceramic fibers: an overview - Roy S.; Kulshrestha M.; Bhargava P.; Das S. (My University, 2025)
Ceramic fibers have been utilized as an essential engineering material due to their exclusive insulation properties because of the presence of a high percentage of porosity (fiber themselves do not have exceptional thermal properties that are different than inherent properties of the corresponding ceramic), chemical inertness, oxidation resistance, and remarkable mechanical properties. To this end, ceramic fibers (both oxide and non-oxide) have received extraordinary attention from academia and industries for applications in various sectors, including, energy, petroleum, textile, aerospace, automobile, and many more. This review focuses on the ceramic fiber manufacturing processes current status and challenges, along with various crucial features and processing parameters. Classification of different ceramic fibers, their applications, properties, and most popularly available manufacturing processes are discussed while covering broad ranges of oxide and non-oxide ceramic fibers. Also, various features and aspects of ceramic fiber manufacturing techniques with different processing parameters are explicitly analyzed with examples. Finally, the challenges and the perspectives of diverse ceramic fiber manufacturing processes are focused and discussed on the future needs in this field of research. © The Korean Ceramic Society 2025.